Cracking patterns in big data saves Colombian rice farmers’ huge losses - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
In 2014, 170 Colombian rice farmers avoided massive losses by taking the advice of their producers’ federation, FEDEARROZ, not to plant in the first of the two annual growing seasons. The farmers who took the advice avoided economic losses estimated at USD 3.6 million. FEDEARROZ acted on a forecast by a team of young CCAFS scientists based at the International Center for Tropical Agriculture (CIAT). The scientists had mined 10 years of weather and crop data to understand how climatic variation impacts rice yields. The team then fed patterns in climate and yields into a computer model and predicted a drought in the Caribbean department of Córdoba, which led it to conclude that farmers in some regions could save themselves from crop failure by not planting at all.